Percutaneous revascularization improves outcomes in patients with prior coronary artery bypass surgery. Issue 3 (3rd December 2012) - Gyenes, Gabor; Norris, Colleen M.; Graham, Michelle M.
<x xml:space="preserve">Abstract</x> Background Although ACC/AHA guidelines recommend a low threshold for catheterization after coronary artery bypass surgery (CABG), in clinical practice repeat revascularization often appears unfeasible and data on outcomes are scarce. Methods Using APPROACH, a clinical data collection and outcome monitoring initiative in Alberta, Canada, we analyzed nonemergency repeat catheterization, revascularization, and mortality rates of all patients with previous CABG, grouped by indication (acute coronary syndromes [ACS], stable angina [SA]) and compared to those of the cohort without previous CABG. Results Of 7, 127 patients, 31.5%, and 11% received percutaneous revascularization (PCI), or reoperation, respectively. Significantly more post‐CABG patients were managed medically as compared with the overall APPROACH cohort of coronary disease patients (57.5% vs. 41.5%—P < 0.001). Post CABG patients with ACS received PCI more often than those with SA (36.4% vs. 24.8%). PCI was associated with improved both non‐adjusted and adjusted mortality by 22 and 19%, respectively (P < 0.001) during a follow‐up of up to 14 years. Patients with diabetes had a higher mortality rate than those without at 1‐, 5‐, and 10‐year follow‐up in every treatment group. However PCI was associated with a similar improvement in mortality (HR: 0.76 [95% SD: 0.65–0.90]) in diabetic patients (HR: 0.85 [95% SD: 0.75–0.96]) when compared to medical management. Conclusion Significantly fewer post‐CABG patients received repeat revascularization than all‐comers however; PCI was associated with improved mortality in both the diabetic and the nondiabetic patient population. These findings support the practice of attempting revascularization in post‐CABG patients, particularly in those with an ACS. © 2012 Wiley Periodicals, Inc.